Estudo do deslocamento do pico Compton em função do estado de preparação da amostra - Lira, Fabiano Sousa (2019)
X-rays techniques are important tools used for studies in several fields, of which it can be stand out of material characterization. Thus, a wide range of different techniques are available today for this purpose, and those based on the use of X-ray fluorescence spectrometry (FRX) are among the most reliable, fast, accurate and versatile analytical methods. However, this technique presents detection limit for light elements chemical analysis. The study of the radiation of the photons scattered by Compton effect is a complementary alternative to the FRX technique, once the Compton profile provides information about the distribution of the scattered electron's momentum. However, the choice of appropriate geometry is crucial for the analysis of scattered radiation, because the scattering is dependent on the angle. Thus, the main objective of this work was to study the displacement of the Compton peak in a X-ray fluorescence spectrometer based on the state of preparation of the sample. This work consisted in the analysis of eight samples of graphite powder of different masses (thicknesses) and two bulk samples (Al and Cu), with the purpose of analyzing the shift of the position of the peak Compton Rh Kα for samples with different masses and apparent densities. In addition, the behavior of the effective scattering angle in relation to the amount of mass, apparent and superficial densities was evaluated. The results suggest that lower values of mass and density can lead to the measurement of effective scattering angles higher than theoretically expected (108º), but tending to the theoretical value with increasing both mass and density. For graphite powder samples, however, even for the largest mass used, 4.5 g, the observed angle was 112.2°, higher than theoretically expected. For the bulk samples, however, due to the high density, a scattering angle is very close to that expected by the theory.